Treatment intensification with radium-223 plus enzalutamide in patients with metastatic castration-resistant prostate cancer - Shore, Neal; Carles, Joan; McDermott, Ray; Agarwal, Neeraj; Tombal, Bertrand (Frontiers in Medicine, 2024)
Several life-prolonging therapies with diverse mechanisms of action (MoA) are available for the treatment of metastatic hormone-sensitive/castration-resistant prostate cancer, with many patients requiring multiple lines of therapy. Nevertheless, treatment optimization to further delay disease progression and improve overall survival remains an unmet need. Despite the number of agents with differing MoAs approved for advanced prostate cancer, many patients receive only one or two life-prolonging therapies. One strategy for enhancing the benefit of treatment for this aggressive disease is combining therapies with different MoAs (treatment intensification) early in the disease course, which may be more effective than administering therapies sequentially, yet still allow for subsequent sequential use of individual therapies to optimize patient outcomes. In this narrative review we discuss the rationale for combining 223radium dichloride (223Ra; an alpha-emitting radionuclide) with enzalutamide (an androgen receptor inhibitor) for treatment intensification, including their differing MoAs, their individual efficacy in this setting, and their largely non-overlapping tolerability profiles. We also summarize the preclinical and clinical data available for this combination to date, including interim safety data from the phase 3 EORTC 1333/PEACE III study which highlight the low fracture risk of 223Ra plus enzalutamide when administered concomitantly with bone health agents. Relevant data were sourced from clinical studies published by the authors and via searches of PubMed, clinical trial registries and congress abstracts.